Gendered Political Exclusion and Democratic Inequality: Reframing Women’s Leadership through a Mubādalah Perspective - Mahmoud Mohamed Ali Mahmoud Edris; Miranti; Baidar Mohammed Mohammed Hassan (Journal of Islamic Mubadalah, 2026)
The underrepresentation of women in politics continues to reflect the enduring influence of patriarchal culture, which shapes gendered political exclusion and undermines the quality of inclusive democracy. This article aims to analyze the structural, cultural, and institutional barriers that contribute to the low representation of women in parliament and government while reconstructing women’s leadership through the perspective of Mubādalah as an ethical-reciprocal approach to democratic equality. This study employed a qualitative method using a socio-legal research design based on library research and was supported by empirical data obtained through interviews, observations, policy documentation, and reports from national and international institutions. The research adopted the perspectives of political feminism, gender-based power relations theory, and the Mubādalah framework. Data sources were derived from state regulations, political reports, election results, and interviews with female political actors in Lampung. The findings indicate that cultural bias, weak support from political parties, and stereotypes concerning competence reinforce the marginalization of women within political spaces. This article recommends strengthening affirmative policies, implementing internal party reforms, promoting gender-sensitive political education, and integrating the values of Mubādalah into democratic governance. These findings affirm that democratic inequality is not a natural phenomenon; rather, it is produced through patriarchal power relations that are institutionally legitimized both socially and politically.